(untitled) (Malaysian Journal of Learning and Instruction, 2024)
Purpose - To improve teacher education and education quality, this study explores the experiences and learning of student teachers during their practice instruction in public high schools in the Philippines. Methodology - Semi-structured, in-depth focus group discussions with student teachers were conducted employing a research design using Colaizzi’s approach. Eight groups of student teachers participated in the focus group discussions (FGDs). Each group comprised five students, with 40 participants in total. Findings - According to the findings, student teachers often struggle with the practical realities of teaching in public school and real-world scenarios instead of controlled training environments. Additionally, teaching-related learning experiences are crucial for adapting to diverse student characteristics and developing teaching styles. A mentoring program is found to be essential, despite issues of communication and confidence. Moreover, having supportive mentors play a significant role in helping student teachers to become effective educators. The study also emphasized the need to enhance the teaching and learning setting through digital tools. Significance - This study provides important insights into the obstacles and potential for improving teacher education quality in the Philippines and expanding the teaching practice program.